The efforts of Islamic Religious Education teachers in fostering students' morals at SMA Negeri 1 Panyabungan Utara - Hutagalung, Juniaerti (MANDAILING GLOBAL EDUKASIA, 2024)
The morals of students are getting worse every year. Parents' anxiety because their children's morals are getting further away from religious values ​​makes parents confused about how to respond to this. Problems always arise in the world of education related to students. In fact, students are the next generation of this nation. The purpose of this study was to determine the efforts of Islamic Religious Education teachers in developing the morals of students at SMAN 1 Panyabungan Utara. The goal is to develop the morals of students at SMAN 1 Panyabungan Uara so that they become students with noble morals, because students as the next generation should have noble, civilized morals in order to become good human beings. The research that the author conducted was field research using a qualitative approach. Data collection was carried out by conducting observations, interviews and documentation. as a data collector from the results of observations. The results of the study showed that the efforts of religious aqidah and moral teachers in fostering students' morals at SMAN 1 Panyabungan Utara were carried out very seriously, because the moral conditions of some students were still not good, such as students often causing trouble at school, and there were still many violations of school rules which made the efforts of religious aqidah and moral teachers in fostering students' morals at SMAN 1 increasingly intense. For this reason, Islamic Religious Education teachers made various efforts in the context of fostering students' morals